The Effect of Kebyar Duduk Peliatan’s Performance During the Covid-19 Pandemic in Bali - Ni Nyoman Manik Suryani (Gondang: Jurnal Seni dan Budaya, 2023)
The purpose of this research was to reveal the phenomenon of the kebyar dudukpeliatan dance during the COVID-19 pandemic. In general, Balinese performing arts activities are very rare because of the red zone and demands for adaptation to health protocols. However, the kebyar duduk dance in the peliatan style was seen being performed. The performance of the kebyar duduk dance in the peliatan style during the COVID-19 pandemic looked different from usual. The questions are: 1) What is the form of the kebyar dudukpeliatan performance during the COVID-19 pandemic?; 2) What was the impact of staging the kebyar duduk peliatanperformance during the COVID-19 pandemic?. This research was completed based on qualitative methods. Secondary data was obtained through literature studies on COVID-19 and the kebyar duduk dance. While the primary data was obtained by means of observation and interviews with informants in Ubud. All data were analyzed qualitatively with aesthetic theory and practice theory. The results of the research show : (1) the people of Ubud present the kebyar duduk peliatan dance through digital technology; (2) the presentation of the kebyar dudukpeliatan dance through digital media has a positive impact on flexibility in learning the kebyar duduk peliatan dance and has a negative impact on the enculturation of the kebyar duduk peliatanperformance in the culture of the Ubud people.